Long-term outcomes of pharmacotherapy in patients with persistent postural-perceptual dizziness - Yagi, Chihiro; Kimura, Akira; Kai, Ryota; Yamagishi, Tatsuya; Ohshima, Shinsuke; Izumi, Shuji; Horii, Arata (Frontiers in Neurology, 2025)
IntroductionPersistent postural-perceptual dizziness (PPPD) is a chronic neuro-otologic disorder characterized by vestibular symptoms such as dizziness, unsteadiness, or non-spinning vertigo. Its pathophysiology is presumed to involve sensory reweighting to visual/somatosensory sensations for maintaining spatial orientation. Serotonergic antidepressants are a major treatment option for PPPD. However, no reports describe the long-term outcomes of these therapeutic agents in patients with PPPD. Therefore, we evaluated the efficacy of antidepressants administered for up to 3 years after initiation in patients with PPPD.MethodsForty-three patients with PPPD (12 men and 31 women; median age at the start of treatment: 49 years) who were started on antidepressants at our department between July 2018 and February 2023 were enrolled. The Dizziness Handicap Inventory (DHI), Hospital Anxiety and Depression Scale (HADS), and Niigata PPPD Questionnaire (NPQ) were used as evaluation measures. Scores at 3 and 6 months and at 1, 1.5, 2, 2.5, and 3 years after starting the medication were compared with pre-treatment scores. Furthermore, head-tilt perception gain (HTPG), an indicator of somatosensory hypersensitivity, was measured before and after treatment.ResultsSignificant improvements in all DHI, HADS, and NPQ measures were observed from 3 months onward and were maintained at all timepoints up to 3 years after treatment. Meanwhile, there was no significant improvement in HTPG after medication treatment was initiated. Patients whose DHI scores improved by ≥18 points were considered treatment responders; 27 of the 43 patients were responders at 1 year after treatment. During the initial 2 weeks of treatment, adverse events, including nausea/abdominal distension, were observed in 26 patients; however, the adverse events did not last until the subsequent observation timepoint. During the case enrollment period, antidepressants were started in 59 patients, and 43 patients included in the present study were able to continue medication (overall adherence rate: 72.9%).ConclusionsThe long-term efficacy and safety of serotonergic antidepressants were demonstrated in patients with PPPD. However, somatosensory hypersensitivity, which is sometimes observed as a clinical feature in patients with PPPD, did not improve after pharmacotherapy. Developing treatments to reduce hypersensitivity may improve treatment outcomes.